Amyloid processing in COVID‐19‐associated neurological syndromes. Issue 2 (2nd March 2022) - Ziff, Oliver J.; Ashton, Nicholas J.; Mehta, Puja R.; Brown, Rachel; Athauda, Dilan; Heaney, Judith; Heslegrave, Amanda J.; Benedet, Andrea Lessa; Blennow, Kaj; Checkley, Anna M.; Houlihan, Catherine F.; Gauthier, Serge; et al.
Abstract: SARS‐CoV‐2 infection can damage the nervous system with multiple neurological manifestations described. However, there is limited understanding of the mechanisms underlying COVID‐19 neurological injury. This is a cross‐sectional exploratory prospective biomarker cohort study of 21 patients with COVID‐19 neurological syndromes (Guillain–Barre Syndrome [GBS], encephalitis, encephalopathy, acute disseminated encephalomyelitis [ADEM], intracranial hypertension, and central pain syndrome) and 23 healthy COVID‐19 negative controls. We measured cerebrospinal fluid (CSF) and serum biomarkers of amyloid processing, neuronal injury (neurofilament light), astrocyte activation (GFAp), and neuroinflammation (tissue necrosis factor [TNF] ɑ, interleukin [IL]‐6, IL‐1β, IL‐8). Patients with COVID‐19 neurological syndromes had significantly reduced CSF soluble amyloid precursor protein (sAPP)‐ɑ ( p = 0.004) and sAPPβ ( p = 0.03) as well as amyloid β (Aβ) 40 ( p = 5.2 × 10 −8 ), Aβ42 ( p = 3.5 × 10 −7 ), and Aβ42/Aβ40 ratio ( p = 0.005) compared to controls. Patients with COVID‐19 neurological syndromes showed significantly increased neurofilament light (NfL, p = 0.001) and this negatively correlated with sAPPɑ and sAPPβ. Conversely, GFAp was significantly reduced in COVID‐19 neurological syndromes ( p = 0.0001) and this positively correlated with sAPPɑ and sAPPβ. COVID‐19 neurological patients also displayed significantly increased CSF proinflammatory cytokines and these negatively correlated with sAPPɑ and sAPPβ. A sensitivity analysis of COVID‐19‐associated GBS revealed a non‐significant trend toward greater impairment of amyloid processing in COVID‐19 central than peripheral neurological syndromes. This pilot study raises the possibility that patients with COVID‐19‐associated neurological syndromes exhibit impaired amyloid processing. Altered amyloid processing was linked to neuronal injury and neuroinflammation but reduced astrocyte activation. Abstract : SARS‐CoV‐2 can result in neurological conditions, but the mechanisms of COVID‐19‐associated nervous system injury remain unclear. Using cerebrospinal fluid (CSF) and blood biomarkers of amyloid processing collected from patients with COVID‐19‐associated neurological injury and healthy controls, we find COVID‐19 neurological patients display impaired amyloid processing characterized by decreased soluble amyloid precursor proteins and Amyloid β. Reductions in amyloid processing biomarkers correlated with increases in neuronal injury (NfL) and neuroinflammatory biomarkers but with decreases in astrocyte reactivity (GFAp). This supports the possibility that patients with COVID‐19‐associated neurological syndromes exhibit impaired amyloid processing during their acute illness.